Root Canal Anatomy of Myanmar Permanent Mandibular Incisors in Mandalay Region - Nyan M. Aung (Hindawi Limited, 2020)
Introduction. Incomplete understanding of the root canal system leads to endodontic failure. Missed canal was the fourth most common endodontic failure, which needed retreatment. There were a few studies on internal morphology of posterior teeth of Myanmar population. However, there was no report on root canal anatomy of anterior teeth. So, the aim of the in vitro study was to investigate root canal anatomy of Myanmar permanent mandibular incisors in Mandalay Region by the staining and clearing method. Materials and Methods. A total of 96 teeth from the tertiary hospitals and one academic department in Mandalay Region were selected according to inclusion and exclusion criteria. Then, they were cleaned, drilled, stained with Indian ink, and decalcified with 5% nitric acid for 3 days. After that, they were dehydrated with ascending concentration of ethanol (80% overnight, 90% for 1 hour, and full strength for three hours). Finally, they were clarified with 98% methyl salicylate and investigated by calibrated observer in case of Vertucci's classification, allocation of apical foramen, and the detailed anatomy. Result. Almost 70% of the teeth had type Ι followed by 21.8% type ΙΙΙ, 4% 1-2-1-2-1 and type ΙΙ, and 1-3-2 and 2-3-1 comprised 1% each. Nearly 70% of apical foramen at central allocation of the root and 14% of detailed anatomy were seen in the sample teeth. Conclusion. Most of the sampled Myanmar teeth comprised one canal and one foramen followed by type ΙΙΙ. However, unusual anatomies, such as 1-2-1-2-1, 1-3-2, and 2-3-1, were also seen. Contrastively, proportions of central location of apical foramen and of detailed anatomy were differed from the former reports. This study summarized that 3 in 10 mandibular incisors comprised the evidence of second or third canal configuration. Three types of intercanal calcifications, fusiform, islet, and bead, were additionally explored.